Genetics and athletic performance: a systematic SWOT analysis of non-systematic reviews - Konopka, Magdalena Johanna; Sperlich, Billy; Rietjens, Gerard; Zeegers, Maurice Petrus (Frontiers in Genetics, 2023)
Exercise genetics/genomics is a growing research discipline comprising several Strengths and Opportunities but also deals with Weaknesses and Threats. This “systematic SWOT overview of non-systematic reviews” (sSWOT) aimed to identify the Strengths, Weaknesses, Opportunities, and Threats linked to exercise genetics/genomics. A systematic search was conducted in the Medline and Embase databases for non-systematic reviews to provide a comprehensive overview of the current literature/research area. The extracted data was thematically analyzed, coded, and categorized into SWOT clusters. In the 45 included reviews five Strengths, nine Weaknesses, six Opportunities, and three Threats were identified. The cluster of Strengths included “advances in technology”, “empirical evidence”, “growing research discipline”, the “establishment of consortia”, and the “acceptance/accessibility of genetic testing”. The Weaknesses were linked to a “low research quality”, the “complexity of exercise-related traits”, “low generalizability”, “high costs”, “genotype scores”, “reporting bias”, “invasive methods”, “research progress”, and “causality”. The Opportunities comprised of “precision exercise”, “omics”, “multicenter studies”, as well as “genetic testing” as “commercial”-, “screening”-, and “anti-doping” detection tool. The Threats were related to “ethical issues”, “direct-to-consumer genetic testing companies”, and “gene doping”. This overview of the present state of the art research in sport genetics/genomics indicates a field with great potential, while also drawing attention to the necessity for additional advancement in methodological and ethical guidance to mitigate the recognized Weaknesses and Threats. The recognized Strengths and Opportunities substantiate the capability of genetics/genomics to make significant contributions to the performance and wellbeing of athletes.